Increasing the Students’ Ability in Mastering Vocabulary Through Guessing Game at XI-MIPA 1 of SMA Negeri 3 Gunungsitoli in 2021/2022 - Syukur Maewi Hulu (Departement of Mathematics Education, 2022)
Vocabulary is a core component of languages and the basic for how the learners speak, listen, read and write. Vocabulary mastery is the ability to use the words in conducting the communication and understandable the meaning of the words or phrases in English. 36 students of class XI-MIPA1 of SMA Negeri 3 Gunungsitoli faced problem in learning vocabulary particularly to obtain and absorb the meaning of new words. To solve the problem, the researcher implemented Guessing Game which the main procedure was asked the students to guess the new word from the explanation of the word itself. To achieve the purpose, the researcher conducted CAR Method and it was applied into two cycles. Each cycle consisted of some phases such as planning, action, observation, and reflection. The instruments used by the researcher to collect the data were observation sheet, field notes and evaluation sheet. In Cycle I, it showed that some of the students were still unable to comprehend the text. However, the students’ ability in mastering vocabulary was increased in Cycle II where the average of the students’ value was 90.33. Therefore, based on the average for the students’ value in the two cycles, it can be categorized in very good level. Hence, Guessing Game can increase the students’ ability in mastering vocabulary.